2021
DOI: 10.1016/j.jtcme.2021.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Menhaden fish oil attenuates postpartum depression in rat model via inhibition of NLRP3-inflammasome driven inflammatory pathway

Abstract: Background and aim Postpartum depression (PPD) is a familiar problem which is associated with about 10–20% of women after child delivery. Fish oil (FO) has a therapeutic potentials to many diseases including mood disorders. However, there is paucity of data on the effects of FO supplementation on PPD rat model. Hence, this study aimed at investigating the potentials of FO in ameliorating depressive-like behaviors in PPD rat by evaluating the involvement of NLRP3-inflammasome. Experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Jialei Zhu et al ( Zhu and Tang, 2020 ) firstly proposed that astrocytic NLRP3 inflammasome was activated in the hippocampus of PPD mouse model. Another study ( Abdul Aziz et al, 2021 ) also showed that increased NF-кB/NLRP3/caspase-1 activity was detected in the hippocampus of PPD rat model. Similarly, a recent study ( Zhai et al, 2022 ) clarified that NLRP3 inflammasome was activated in the hypothalamus of PPD rat model.…”
Section: Inflammatory Pathophysiological Mechanisms In Postpartum Dep...mentioning
confidence: 89%
“…Jialei Zhu et al ( Zhu and Tang, 2020 ) firstly proposed that astrocytic NLRP3 inflammasome was activated in the hippocampus of PPD mouse model. Another study ( Abdul Aziz et al, 2021 ) also showed that increased NF-кB/NLRP3/caspase-1 activity was detected in the hippocampus of PPD rat model. Similarly, a recent study ( Zhai et al, 2022 ) clarified that NLRP3 inflammasome was activated in the hypothalamus of PPD rat model.…”
Section: Inflammatory Pathophysiological Mechanisms In Postpartum Dep...mentioning
confidence: 89%
“…This is an interesting concept, as the Mediterranean diet is characterized by a good balance of n-6 to omega-3 PUFA intake, while more Westernized and high-fat diets involve much higher intake of n-6 PUFAs (Mariamenatu and Abdu, 2021). PUFAs also have additional immunomodulatory and neuroplastic properties, which may be related to their effects on mitochondrial function as discussed in previous sections (Su et al, 2015;Pérez et al, 2018;Abdul Aziz et al, 2021).…”
Section: Polyunsaturated Fatty Acidsmentioning
confidence: 99%